Team Effectiveness in Organizing Care Service Systems for Patients with COVID-19 as Perceived by Professional Nurses - tantapong, usa; patiganmonthon, Namfon; Singchungchai, Phechnoy; Wimonthada, Surang (NU Journal of Nursing and Health Sciences, 2023)
This descriptive research aimed to explore team effectiveness and to compare team effectiveness in organizing care service systems for COVID-19 patients classified according to work experience and departments that provided care services. The concept of Northouse’s team effectiveness was used as the framework. The study was conducted in community hospitals in Health District 5 under the Ministry of Public Health from November 2021 to January 2022. A sample group of 336 professional nurses was selected using purposive sampling. The questionnaire used for data collection consisted of 2 parts: (1) General data, and (2) Team effectiveness in team performance and team development. The question items on team effectiveness were adapted from Tantapong’s questionnaire. The research instrument was validated by 3 experts and the CVI was 0.88, and Cronbach’s alpha coefficient was 0.90. The data were analyzed using descriptive statistics of frequency, percentage, mean, standard deviation, and inferential statistics of ANOVA. The study found that the sample group perceived the team’s effectiveness in organizing care service systems for COVID-19 patients in terms of performance at a high level ( = 3.34, S.D. = 0.56), and team development at a high level ( = 3.27, S.D. = 0.63). The sample with different work experience and worked in different departments that provided care services for COVID-19 patients were not different in their perception of team effectiveness with statistical significance (p > 0.05). It is recommended that future studies should be conducted on factors related to team effectiveness, or on supporting factors for professional nurses to perceive team effectiveness in organizing care service systems for COVID-19 patients concerning team performance and team development.